Characterization of the chloroplast genome of the family Lauraceae plant species, Cinnamomum cassia. Issue 2 (3rd July 2019) - Song, Kai; He, Man; Yu, Jingbo; Guan, Yanjun; Bai, Yumeng; Xin, Shuquan; Cao, Tianyi
Abstract: The fruit of Cinnamomum cassia is an important spice material and its branch is a common Chinese herbal medicine as the family Lauraceae. In this study, we reported the complete chloroplast genome of C. cassia. The chloroplast genome of C. cassia with length of 152, 675 bp is a characteristic quadripartite structure. The length of the inverted-repeats regions (IRs), large single-copy (LSC) region, and small single-copy (SSC) region of C. cassia was 20, 068 bp, 93, 663 and 18, 876 bp. The chloroplast genome of C. cassia contains 124 genes, which includes 80 protein-coding genes (PCGs), 36 transfer RNA genes (tRNAs) and 8 ribosomal RNA genes (rRNAs). The overall nucleotide content of the chloroplast genome: 30.0% A (Adenine), 30.8% T (Thymine), 19.7% C (Cytosine), 19.5% G (Guanine), and 39.2% GC content. Evolutionary relationship result showed that Cinnamomum cassia was most closely related to Cinnamomum parthenoxylon in the family Lauraceae by the Neighbor-Joining (NJ) method.